French View of Sustainable Work in a Context of Work Transformations Discussed as a Part of Social Dialogue - Céline Teyssier (Italian Labour Law e-Journal)
This contribution aims to explore the presence of sustainable work in the collective bargaining as a new field of negotiation and to identify the conditions and means necessary for a fruitful social dialogue. Putting sustainable work on the agenda of companies contribute to a greater visibility and practical implementation of the concept, in a context of transformations of the world of work.